Atlas of organ transplantation - Humar, Abhinav; Sturdevant, Mark L.; Humar, Abhinav (London ; Heidelberg : Springer, 2015)
This comprehensive, step-by-step account of current abdominal organ transplant surgery provides the reader with a clear visual and written description of the major transplant procedures. Atlas of Organ Transplantation, Second Edition emphasises new procedures, and those that have undergone significant modifications. With the help of schematic diagrams, high-quality intra-operative photographs and videos, the reader is able to clearly visualize the course of the operative procedures. Written by experts in the field, this Atlas is essential reading for all transplant surgeons, residents and fellows, as well as operating room nurses and transplant nurses
1. Standard Multiorgan Procurement from the Deceased Donor -- 2. Donation After Cardiac Death Organ Procurement and Transplantation -- 3. Dialysis Access Procedures -- 4. Nephrectomy from a Living Donor -- 5. Kidney Transplantation -- 6. Pancreas Transplantation -- 7. Liver Transplantation -- 8. Intestinal and Multivisceral Transplantation -- 9. Total Pancreatectomy and Islet Autotransplantation -- 10. Pediatric Liver Transplantation
Includes index
Preceded by: Atlas of organ transplantation / Abhinav Humar, Arthur J. Matas, and William D. Payne. c2006
1 13
Keywords: Organ Transplantation